A Survey on Energy Efficient, Secure Routing Protocols for Wireless Sensor Networks (International Journal of Engineering and Computer Science, 2018)
The Wireless Sensor Network (WSN) in present generation has gained its popularity due its applicability nature in various areas Such as monitoring system of Oceans, wide life, manufacturing plants, earthquake prediction unit, military units, etc. The cost and structural complexity of a WSN are very low. In general, a WSN consists a sensor node (SN) that gathers the data from the atmosphere/environment. An SN exhibit very low power battery (LPB) and if the battery power gets drained SN will stop its functionality. Once the battery power is drained, it is impossible to recharge it back due to the wide spread network structure. The un-functionality of an SN may lead to failure of the routing protocol. Commonly a routing protocol facilitates an efficient routing path among the SNs. The security of data over the WSN is an always biggest issue which needs to be resolved. Many of the researchers have explained their views for energy efficient, secure routing protocol for a WSN. This survey paper discusses the various energy efficient techniques, secure routing techniques, classifications of routing protocol, attacks on WSN. The surveys towards the recent work on energy efficient & secure routing protocols are discussed with the research gap. Finally, future work is demonstrated followed by a conclusion.